MERANCANG STRATEGI PERSAINGAN YANG KOMPETITIF MENGGUNAKAN BUSINESS MODEL CANVAS (BMC): STUDI KASUS PADA CV. AJ - Felicia Katherine Geonawan; Wirawan Endro Dwi Radianto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to design a competitive strategy development using the Business Model Canvas (BMC), with a case study on CV. AJ in South Kalimantan. The research adopts a qualitative approach with a case study method to explore the phenomenon experienced by CV. AJ in developing its competitive strategy through the BMC conceptual framework. The findings indicate that the strategy of expanding the product portfolio by introducing new feed brands can be sustained and further developed by emphasizing a differentiated value proposition, specifically superior feed quality and financial support. The addition of brand B feed does not lead to significant changes in the company’s key activities as a feed distributor. This study also provides operational recommendations for each element of CV. AJ’s business model that can be implemented to address the increasingly dynamic and competitive market environment.